Literature Study: Teachers' Perceptions of Policy Analysis of Deep Learning Strategies in Improving Learners' Critical Thinking - Kamelia Musaad; Kaniati Amalia; Ayu Wulandari; Muffarihul Hazin; Haris Supratno (International Journal of Education, Language, and Religion, 2025)
The rapid development of information and communication technology has driven a transformation in the educational paradigm, one of which is through the implementation of deep learning-based learning strategies. Deep learning not only increases the effectiveness of the learning process, but also has great potential in developing students' critical thinking skills, which are key competencies in facing the challenges of the 21st century. However, the successful implementation of this strategy is greatly influenced by teachers' perceptions and attitudes towards the innovation. This literature study aims to examine in depth teachers' perceptions of deep learning policy and strategy implementation, the factors that influence these perceptions, and the implications for developing learners' critical thinking skills. The analysis shows that teachers' positive perceptions, supported by adequate training, adequate facilities, and systematic support, can improve the readiness and effectiveness of implementing deep learning strategies in learning. In contrast, negative perceptions and resistance to change are the main obstacles that need to be overcome through comprehensive interventions. The results of this study emphasize the importance of paying attention to perceptual aspects and supporting factors in order to increase the success of technology-based pedagogical innovations